Characteristics and Factors Affecting Neglected DJ Stent at Tertiary Hospital in Eastern Part of Indonesia - Ardito Ario Willy Goller; Wahjoe Djatisoesanto; Rizal Rian Dhalas; Asma Jedidi (Biomolecular and Health Science Journal)
Introduction: Double J (DJ) stenting is a widely performed urological procedure used to maintain urinary drainage. Complications such as stent encrustation, fragmentation, stone formation, and urinary tract infections are common, particularly when DJ stents are neglected. Limited data are available on neglected DJ stent outcomes, emphasizing the need to investigate factors contributing to encrustation within this population. Methods: A retrospective study was conducted at Dr. Soetomo General Academic Hospital using medical records. Data were collected for 120 patients who had undergone DJ stenting. The information gathered included demographic details, indications for DJ stenting, and the incidence of encrustation. Chi-square tests were used to evaluate the relationships between stent encrustation incidence and other variables. In addition, a binary logistic regression was performed to identify independent risk factors for DJ stent encrustation. Results: Of the 120 participants, 53.3% were female, and 71.7% were aged 18–65. The most common educational level was junior high (41.7%). Encrustation was absent in 57.5% of cases. Statistical analysis revealed that gender (P = 0.042) and education level (P = 0.014) significantly influenced encrustation rates. Male patients had a 2.136-fold increased risk of encrustation, whereas those with elementary education had a 10.804 times higher risk. Conclusions: This study identifies gender and education level as key factors in DJ stent encrustation risk. Males and patients with lower education levels are at higher risk. Targeted education and follow-up initiatives for high-risk groups are essential to mitigate these complications.